Campeonas. Cambiando las reglas del juego - Castro Bernardini, María José (2023)
Fernanda Arris Calderon (Perú) - Moderadora / María José Castro Bernardini (Perú) - Autora / Bruno Rivas Frías (Perú) - Autor / Daniel Cino Barreda - Panelista